Chemical composition, antimicrobial and antioxidant activity ofessential oils from cumin and ajowan - SAHADEO D. PATIL; PANKAJ P. MAKNIKAR; SUSHILKUMAR J. WANKHADE; CHANDRAKIRAN S. UKESH; MAHENDRA K. RAI (Nusantara Bioscience, 2016)
Abstract. Patil SD, Maknikar PP, Wankhade SJ, Ukesh CS, Rai MK. 2016. Chemical composition, antimicrobial and antioxidant activity of essential oils from cumin and ajowan. Nusantara Bioscience 8: 60-65. Plant essential oils have gained importance as alternative remedies for treatment of many infectious diseases and food preservatives. In the present study, we have determined the chemical composition of the essential oils (EOs) from two Indian spices Cuminum cyminum (cumin) and Trachyspermum ammi (ajowan) of family Apiaceae by gas chromatography-mass spectrometry (GC-MS). Moreover, the antimicrobial potential of these oils was evaluated against several Gram-positive and Gram-negative bacteria using disc diffusion and broth microdilution methods. A Total of 20 major chemical components were analyzed by GC-MS studies and were found to be cuminaldehyde (36.67%) and caren-10-al (21.34%) in case of cumin essential oil while p-cymene (15.54%) and thymol (15.48%) were found to be present in ajowan essential oil. Both the EOs exhibited potent antibacterial effect against most of the tested pathogens. Furthermore, cumin and ajowan EOs demonstrated remarkable antibacterial activity against Salmonella typhi with an inhibition zone diameter of 54 and 60 mm respectively with identical MIC value of 12.5 µl/ml. Ajowan EO was found to exhibit wide spectrum activity against both the Gram-positive and Gram-negative organisms when compared with cumin. Both the essential oils were more potent than standard antibiotic chloramphenicol except cumin against Escherichia coli and Enterobacter aerogenes. Antioxidant activity of cumin was weaker (12.36%) and ajowan was stronger (71.68%) than standard ascorbic acid (20.24%) at 1000 µg/ml concentration when assessed by DPPH radical scavenging assay. Our study suggests that spice essential oils have significant potential in controlling the human and foodborne pathogens.